Critiques of the circular economy. (17th August 2021) - Corvellec, Hervé; Stowell, Alison F.; Johansson, Nils
Abstract: This paper presents a reasoned account of the critiques addressed to the circular economy and circular business models. These critiques claim that the circular economy has diffused limits, unclear theoretical grounds, and that its implementation faces structural obstacles. Circular economy is based on an ideological agenda dominated by technical and economic accounts, which brings uncertain contributions to sustainability and depoliticizes sustainable growth. Bringing together these critiques demonstrates that the circular economy is far from being as promising as its advocates claim it to be. Circularity emerges instead as a theoretically, practically, and ideologically questionable notion. The paper concludes by proposing critical issues that need to be addressed if the circular economy and its business models are to open routes for more sustainable economic development.